Suppression of transient receptor potential melastatin 7 regulates pluripotency, proliferation, and differentiation of mouse embryonic stem cells via mechanistic target of rapamycin‐extracellular signal‐regulated kinase activation. Issue 3 (27th December 2021) - Kim, Wansoo; Park, Song; Kwon, Wookbong; Kim, Daehwan; Park, Jin‐Kyu; Han, Jee Eun; Cho, Gil‐Jae; Han, Se‐Hyeon; Sung, Yonghun; Yi, Jun‐Koo; Kim, Myoung Ok; Ryoo, Zae Young; et al.
Abstract: Mouse embryonic stem cells (mESCs) are a widely used model for their diverse availability in studying early embryonic development and their application in regenerative treatment of various intractable diseases. Transient receptor potential melastatin 7 (Trpm7) regulates Ca 2+ as a nonselective ion channel and is essential for early embryonic development; however, the precise role of Trpm7 in mESCs has not been clearly elucidated. In this study, we showed that the inhibition of Trpm7 affects the pluripotency and self‐renewal of mESCs. We found that short hairpin RNA (shRNA)‐mediated suppression of Trpm7 resulted in decreased expression of transcriptional regulators, Oct4 and Sox2, which maintain stemness in mESCs. In addition, Trpm7 knockdown led to alterations in the basic properties of mESCs, such as decreased proliferation, cell cycle arrest at the G0/G1 phase, and increased apoptosis. Furthermore, embryoid body (EB) formation and teratoma formation assays revealed abnormal regulation of differentiation due to Trpm7 knockdown, including the smaller size of EBs, elevated ectodermal differentiation, and diminished endodermal and mesodermal differentiation. We found that EB Day 7 samples displayed decreased intracellular Ca 2+ levels compared to those of the scrambled group. Finally, we identified that these alterations induced by Trpm7 knockdown occurred due to decreased phosphorylation of mechanistic target of rapamycin (mTOR) and subsequent activation of extracellular signal‐regulated kinase (ERK) in mESCs. Our findings suggest that Trpm7 could be a novel regulator for maintaining stemness and modulating the differentiation of mESCs.